Investigação de comorbidades associadas a pacientes com Covid-19 em um hospital de urgência em Belém-Pa no período de março de 2021 a abril de 2022 - CARDOSO, Paulo Araújo (2023)
Introduction: In this century, humanity is once again experiencing the strain of pandemics caused by viruses. Like the Severe Acute Respiratory Syndrome SARS-CoV, China in 2002; Middle East Respiratory Syndrome MERS-CoV, Saudi Arabia in 2012; and Covid-19 SARS- CoV-2, China in 2019. In this context, infectious diseases gain greater prominence when associated with risk factors such as the presence of comorbidities. Justification: Studies show that cardiovascular, metabolic, endocrine diseases, as well as advanced age and obesity increase mortality from viral infections, generating public health problems. Objective: To know the comorbidities of patients infected with SARS-CoV-2 from April/21 to March/22 in a public hospital in Belém-Pa. To analyze the correlation of these comorbidities with Covid-19 mortality using the Spernam coefficient. Identify the profile of the population of patients most vulnerable to Covid-19 associated with comorbidities. Methods: The nominal list of patients with RT- PCR positive for Covid-19 was taken from the Laboratory Environment Manager. Comorbidities were investigated in the notes made in the risk classification of these patients. These data were taken from the medical records filed in the Multiprofessional Statistical and Digitization Archive Service of the Municipal Emergency Hospital Mário Pinotti and compared with the death certificates for Covid-19. The variables were compared using Spearman's coefficient considering a value of p < 0.05. Results: 57% of patients had comorbidities. Systemic Arterial Hypertension 27%, Diabetes Mellitus II 10%, Lung Disease 7% were more frequent and their associations 6.5% of the total. Men were more affected and the age group with the highest rate of infection was 41 to 60 years. The lethality coefficient was higher in people over 80 years of age and zero in those under 21 years of age. Conclusion: The association of comorbidities and the presence of SARS-CoV-2 infection showed negative outcomes in hospitalizations. The profile of patients at higher risk of illness from Covid-19 are adults between 40 and 60 years old, men who have at least one comorbidity.